2015
DOI: 10.1080/00480169.2014.987840
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic resistance in equine helminth parasites – a growing issue for horse owners and veterinarians in New Zealand?

Abstract: There is growing concern that given the high frequency with which anthelmintics are being administered to many horses, anthelmintic resistance amongst equine helminth populations will be an increasing problem, rendering many of the currently available products unusable with little prospect of new products becoming available, at least in the near future. Worldwide, much reliance has been placed on the macrocyclic lactone (ML) group of anthelmintics, but resistance has been reported to these products as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 90 publications
1
16
0
13
Order By: Relevance
“…Half of both Thoroughbred and Standardbred trainers were using an interval regimen for spellers and racehorses. The reliance on the interval strategy is consistent with previous studies of Thoroughbreds and Standardbred stud farms in New Zealand . Similarly, the median number of treatments horses received annually was comparable with the number of treatments on stud farms, with racehorses treated as frequently as yearlings at up to 15 times annually .…”
Section: Discussionsupporting
confidence: 85%
“…Half of both Thoroughbred and Standardbred trainers were using an interval regimen for spellers and racehorses. The reliance on the interval strategy is consistent with previous studies of Thoroughbreds and Standardbred stud farms in New Zealand . Similarly, the median number of treatments horses received annually was comparable with the number of treatments on stud farms, with racehorses treated as frequently as yearlings at up to 15 times annually .…”
Section: Discussionsupporting
confidence: 85%
“…It has been accepted that resistance of the cyathostomes to the benzimidazole anthelmintics is widespread in New Zealand (Bishop et al, 2013;Scott et al, 2015). Furthermore, a recent study on three Thoroughbred stud farms in New Zealand indicated that resistance of Parascaris equorum to ivermectin has developed (Bishop et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente la resistencia a los BZs resulta la más prevalente en los ciatostomas (Traversa et al, 2012), reportándose en al menos 14 países (Peregrine et al, 2014). Por su parte, la periodicidad de los tratamientos antihelmínticos en el Rancho Turiguanó imprime una alta presión de selección sobre la población parasitaria (Scott et al, 2015).…”
Section: Discussionunclassified
“…Esta práctica y el empleo inadecuado de drogas antiparasitarias condujo a la aparición de nematodos resistentes en ganaderías equinas en todo el mundo (Kaplan y Nielsen, 2010; Scott et al, 2015). La gran mayoría de los helmintos gastrointestinales de los equinos están representados por los miembros de la familia Strongylidae, con al menos 63 especies (Lichtenfels et al, 2008), de las cuales se reportan 24 en Cuba (Pérez-Vigueras, 1936; Varus y Valle, 1966).…”
Section: Introductionunclassified